Resistance to Canadian mining projects in Mexico: lessons from the lifecycle of the San Xavier Mine in San Luis Potosí - Darcy Victor Tetreault (Journal of Political Ecology, 2019)
This article analyses resistance movements to large-scale mining projects in Mexico, particularly the case of sustained organized resistance to the San Xavier Mine, in the central north state of San Luis Potosí. As one of the first struggles in Mexico against Canadian mining projects after the signing of the North American Free Trade Agreement, the leaders of this movement pioneered strategies of resistance on the legal front and were instrumental in building anti-mining alliances and networks on the national and international levels. Now that the excavation process has finished and the mine is closing down, this article seeks to draw on the case to illustrate the complementarity of three approaches for interpreting resistance to mining: class struggle, ecological distribution conflicts, and the clash of cultural valuations over territorial vocation. The argument is that these approaches are not mutually exclusive; they can be combined to explain the multiple dimensions of specific struggles, whose shifts in emphasis at different moments of the struggle are conditioned by – and condition – the phase of a mine's development. By contextualizing the case study in a broader analysis of social environmental conflicts around mining in Mexico and elsewhere in Latin America, the analysis seeks to illustrate the ways in which the struggle against the San Xavier Mine is representative of broader trends, as well as its peculiarities. On the local level, we find the struggle has more to do with defending conditions of social and cultural reproduction than protecting the means of production that sustain traditional livelihoods. This pertains, not just to a non-contaminated living environment and the availability of clean water for human consumption, but also to the conservation of natural and architectural patrimony with historic and cultural significance.